PENDIDIKAN KARAKTER CINTA TANAH AIR MELALUI LAGU NASIONAL DI SDN REJOSARI 02 SEMARANG - Ami Dwi Lestari; M. Yusuf Setiawardana; Ari Widyaningrum (Universitas PGRI Yogyakarta, 2020)
Character education is very influential with the creation of the character of an individual or student. The early age is a very critical age to build individual character. Instill to the young generation of what it means to be good citizens that is they show their pride and loveÂ of the country. The inculcation of the character of love for the country through national songs is considered as one of the appropriate media to foster a sense of love for the country. Simple song lyrics are easily understood by children so that the meaning of national song lyrics can be conveyed to students, can bring out a high sense of love for the country, national spirit, and buildÂ the nationalism character. The focus of this research is how to educate the character of love for the country through the national song at SDN 02 Rejosari. The purpose of this research is to find out how the character education of the love of the country through the national song at SDN 02 Rejosari Semarang. This type of research is qualitative research, using the method of observation, interviews and documentation. The subjects of this study were students of VI class who were randomly selected. The results showed that character education for the love of the country through the national song has been implemented at SDN 02 Rejosari. The inculcation of the value of character education for the love of the country through habituation to singing the national song. The habit of singing and understanding the meaning of national song lyrics can influence students by carrying out behaviors / actions that reflect to the love of the country in daily life.